Tracking Scientific Attention on Kaziranga National Park: A Bibliometric Study - Deka, Pranjal; Sarmah, Mukut (Journal of Data Science, Informetrics, and Citation Studies)
Kaziranga National Park, a UNESCO World Heritage Site in Assam, India, is renowned for its rich biodiversity. The park plays a significant role in wildlife conservation in Assam and India. The national park is divided into four ranges: Kohora, Bagori, Agaratoli, and Burhapahar. This park is home to a diverse range of wildlife. This study employs a bibliometric analysis of publications from 1993 to 2025, retrieved from the Web of Science database, to examine research trends, key contributors, and the thematic diversity of research on Kaziranga. The analysis reveals steady scholarly growth, with 44 documents authored by 156 researchers affiliated with leading institutions, including Tezpur University, the CSIR, India, and the University of Edinburgh. The research areas encompass local conservation efforts focused on the Big 5 species and ecological risks, as well as interdisciplinary themes such as paleoecology, geochemistry, and environmental history. Thematic mapping effectively highlights well-developed major themes, such as biodiversity and megafaunal extinction, niche-specialized topics, and emerging areas, indicating a dynamic and evolving research landscape in Kaziranga. The analysis emphasises Kaziranga's importance for ecological conservation and provides an overview of scholarly engagement with its exceptional environment across multiple contexts.
Keywords: Assam; Authorship; Bibliometrics; India; Institutions; Kaziranga; Keywords; Research Trends.